2022
DOI: 10.1007/s11249-022-01655-7
|View full text |Cite
|
Sign up to set email alerts
|

Starvation and Re-lubrication in Oscillating Bearings: Influence of Grease Parameters

Abstract: A common application for grease-lubricated oscillating rolling element bearings is, e.g., rotor blade bearings in wind turbines. These bearings mainly operate under conditions that are prone to starvation. If the grease is unable to provide enough inlet lubricant supply for the contact between rolling element and bearing raceway, wear in the form of False Brinelling and thus premature bearing failure is possible. Bearing experiments with different lithium complex model greases, which differ mainly in their bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Parameter studies (see [6,18]) have shown that, under certain operating conditions, it is possible for grease-lubricated oscillating rolling bearings to operate without damage, at least in the short term. However, if the operating conditions result in severe starvation and solid contact between the rolling element and raceway, adhesion between the contact partners can occur due to the similarity in the materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parameter studies (see [6,18]) have shown that, under certain operating conditions, it is possible for grease-lubricated oscillating rolling bearings to operate without damage, at least in the short term. However, if the operating conditions result in severe starvation and solid contact between the rolling element and raceway, adhesion between the contact partners can occur due to the similarity in the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Other publications have dealt with lubrication mechanisms and the effectiveness of greases in preventing wear damage. Summarized from the publications of MARUYAMA, SAATCHI, WANDEL, KITA, and SHIMA, a high oil release as well as a low grease consistency and a high mobility of the base oil are crucial to prevent wear [14][15][16][17][18]. The suitability of lubricants for oscillating bearing applications is often determined using standard tests such as the Fafnir test and the SNR-FEB2-test [19,20].…”
Section: Wear In Oscillating Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter studies (see [6,18]) have shown that under certain operating conditions it is possible for grease-lubricated oscillating rolling bearings to operate without damage, at least for a short term. However, if the operating conditions result in severe starvation and solid contact between the rolling element and raceway, adhesion between the contact partners can occur due to the similarity of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Other publications deal with lubrication mechanisms and the effectiveness of greases in preventing wear damage. Summarized from the publications of MARUYAMA, SAATCHI, WANDEL, KITA, and SHIMA, a high oil release as well as a low grease consistency and a high mobility of the base oil are crucial to prevent wear [14][15][16][17][18]. The suitability of lubricants for oscillating bearing applications is often determined using standard tests such as the Fafnir-test and the SNR-FEB2-test [19,20].…”
Section: Wear In Oscillating Bearingsmentioning
confidence: 99%